Moderation- mediation effects of english proficiency and willingness to communicate on the relationships between self-efficacy and communication apprehension and frequency of english communication - Agwel, Khideja M.A. (2021)
Frequency of English usage to execute banking work- related varies according to a number of linguistic, communication and psychological factors. Affective factors such as willingness to communicate, self-efficacy and communication apprehension may explain why some employees seek, while others avoid English language communication. Despite employees’ excellent English proficiency, frequent use of English is not ensured. This study examines the moderation-mediation effects of willingness to communicate and English proficiency on the relationships between communication apprehension, selfefficacy and frequency of English communication in the banking context. This study employed an explanatory sequential quantitative driven design. In this design, the researcher collected data through the questionnaire and a semi-structured interview from Libyan bank’ employees using a purposive sampling strategy. The employees in Gumhouria bank were selected as participants and useful subjects for the study. Frequency, percentage, means, and standard deviation (SD) were used to report descriptive data. The Structural Equation Modelling of Partial Least Squares (PLS-SEM) was utilised to examine the mediating effect of willingness to communicate and moderating role of English proficiency between the independent variables and frequency of English communication, as well as the relation between communication apprehension, English self- efficacy, willingness to communicate and frequency of English communication. Findings of the study indicate that more than a half number of the participants had a moderate level of communication apprehension and English proficiency while a majority had high level of willingness to communicate and English self- efficacy. The findings also revealed that communication apprehension and English self- efficacy were a powerful predictor of frequency of English communication. Communication apprehension was negatively correlated with frequency of English communication whereas self- efficacy had a positive and significant relationship with frequency of English communication. Additionally, a positive relationship exists between willingness to communicate and frequency of English communication. Willingness to communicate partially mediated the relationship between communication apprehension and frequency of English communication as well as it fully mediates the relationship between English self-efficacy and frequency of English communication. The findings are in support of the MacIntyre’ theoretical model that willingness to communicate is a powerful predictor of individuals’ second or foreign language use. The study also demonstrates that English proficiency moderated the relationship between willingness to communicate and frequency of English communication positively. The study contributes significantly to the body of knowledge, in terms of the developed theoretical model of Willingness to Communicate, Self- efficacy and Communication Apprehension theories and frequency of English communication in the banking workplace. The study suggests that bank employees need to enhance their willingness to communicate and self-efficacy in English because a higher level of willingness to communicate and self-efficacy with low level of communication apprehension would lead to more English use in the banking workplace.